The Role of Forgiveness in Moderating Self-Acceptance and Self-Control among Adolescents of Divorced Parents - Hidayat, Fauziah Nadrotun Nisa; Nashori, Fuad (International Journal of Islamic Educational Psychology, 2025)
Divorce is often viewed as a last resort for marital conflict resolution, yet it can lead to significant psychological effects on children, particularly in reducing self-control. This study aimed to examine the moderating role of forgiveness in the relationship between self-acceptance and self-control among adolescents with divorced parents. Two hundred fifteen (215) adolescents in Yogyakarta, Indonesia, were selected using non-probability quota sampling. Data were collected using the Brief Self-Control Scale (BSCS), Transgression-Related Interpersonal Motivation (TRIM-18) for forgiveness, and Berger’s Self-Acceptance Scale. Moderation regression analysis was conducted using JAMOVI version 2.3.18. The results revealed a significant negative moderating effect of forgiveness: higher levels of forgiveness weakened the positive influence of self-acceptance on self-control. This finding challenges the conventional belief that forgiveness always enhances psychological adjustment. In certain cases, forgiveness—especially when driven by external expectations or unresolved emotions—may hinder internal self-regulation processes fostered by self-acceptance. Theoretically, this study contributes to the understanding of complex emotional dynamics in adolescents from divorced families. Practically, it suggests that mental health interventions should prioritize the development of authentic self-acceptance and emotional readiness before promoting forgiveness. Programs to support adolescents post-divorce should consider individual differences, the timing of forgiveness, and cultural contexts when designing effective psychological or educational intervention